A wolf called wander eaudiobook - Parry, Rosanne (Voice of the Wilderness., 2019)
A New York Times bestseller! "Don't miss this dazzling tour de force."—Katherine Applegate, Newbery Medal winning author of The One and Only Ivan This gripping novel about survival and family is based on the real story of one wolf's incredible journey to find a safe place to call home. This irresistible tale by award-winning author Rosanne Parry is for fans of Sara Pennypacker's Pax and Katherine Applegate's The One and Only Ivan. Swift, a young wolf cub, lives with his pack in the mountains learning to hunt, competing with his brothers and sisters for hierarchy, and watching over a new litter of cubs. Then a rival pack attacks, and Swift and his family scatter. Alone and scared, Swift must flee and find a new home. His journey takes him a remarkable one thousand miles across the Pacific Northwest. The trip is full of peril, and Swift encounters forest fires, hunters, highways, and hunger before he finds his new home. Inspired by the extraordinary true story of a wolf named OR-7 (or Journey), this irresistible tale of survival invites readers to experience and imagine what it would be like to be one of the most misunderstood animals on earth. This gripping and appealing novel about family, courage, loyalty, and the natural world is for fans of Fred Gipson's Old Yeller and Katherine Applegate's Endling. Includes information about the real wolf who inspired the novel. Plus don't miss Rosanne Parry's stand-alone companion novel, A Whale of the Wild.